INTERNALISASI NILAI KEMUHAMMADIYAHAN DALAM BUDAYA ORGANISASI PESANTREN MUHAMMADIYAH - Anisa Nur Rahmawati; Arrum Kharisma; Muhammad Hafizh Hanafi; Sambudi sambudi; Djamaluddin Perawironegoro (Universitas Dharmawangsa, 2023)
In This pesantren education institution, it is very important to have a organizational culture because with the organizational culture a pesantren institution is able to deal with changing times and with this organizational culture it can be seen the value of excellence from the pesantren institution. Internalization of the value of kemuhammadiyahan has a very close relationship with values, therefore a large organization has a structured and planned role. Muhammadiyah values that can be internalized include piety, amar ma’ruf nahi munkar, tajdid, tasamuh, taawun. The purpose of this article is to improve the organizational culture of pesantren so that they are able to compete with other pesantren educational institutions. This study uses a qualitative approach. The type of research is library (library research). The collection technique uses library techniques. This library method uses in the prepation of scientific works through data analysis from various journals, or books. The source of this data comes from various journal article related to the organizational culture of the Islamic boarding school. The data analysis is content analysis.